Quality characteristics in rapeseed-mustard and role of some anti-nutritional factors in plant defense: future strategies - Sandeep Kumar; Dhiraj Singh; M Dutta (Journal of Oilseed Brassica, 2026)
Recommendations for use of rapeseed-mustard oil and seed meal for consumption purposes particularlypresence of low saturated fat, high oleic acid, balanced ratio of SFA/MUFA/PUFA and antioxidants, andabsence of trans-fat and minimum anti-nutritional factors, are generally different from those of industrialrequirements. Further, some anti-nutritional factors present in rapeseed-mustard crops are known to beassociated with some plant defense system and other important biological functions. These factors havebrought the crop quality research on top with the objective of producing designer crops specific forconsumption and industrial purposes. For producing such designer crops through conventional breeding,screening of the available germplasm for specific traits and their further utilization in crop improvementprogramme becomes necessary. An integrated approach including plant breeding, genetics, biochemistry andbiotechnology including bioinformatics is essential in identifying new related biomarkers, or elucidating thechemistry of regulation of various biotic and abiotic stresses. In the present review, information regardingrapeseed-mustard quality characteristics and on correlation of some anti-nutritional factors with some bioticand abiotic stresses has been compiled.